Penyuluhan mitigasi bencana melalui media edukasi di Desa Nagrak Kecamatan Cianjur - Ika Mustika; M. Zaki Alfriandi; Neng Fitriah Nurahman (Abdimas Siliwangi, 2023)
Disaster mitigation counseling through educational media is part of the community service activities organized by IKIP Siliwangi. The counseling aims to provide information, knowledge and understanding to the community about disaster mitigation as an effort to reduce disaster risk and save lives. In addition, to increase public awareness of actions that must be taken pre-disaster, during disasters, and after disasters occur. The method used in counseling includes four stages of activity, which is the service problem identification stage, the service planning stage, the service implementation stage, and the service evaluation stage. The target of the counseling is the community of Nagrak Village, Cianjur Subdistrict, Cianjur Regency, West Java considering that this area is one of the areas that was quite severely affected by the earthquake disaster. Based on interview data and discussions during the service activities, the community showed a positive response to disaster mitigation counseling through the use of educational media.